Pemanfaatan Laman Guna Penentuan Produk Unggulan dan Target Importir Potensial - Hidayat, Yusmar Ardhi; Shelomita, Ardhia; Pikri, Pikri (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
Two partners in the activity have competitive products, namely lurik fabrics and virgin coconut oil. The partners encountered challenges in determining destination countries and obtaining potential importers for the two competitive products. Google Ads Planner, the Harmonized System (HS) codes, and websites were used to conduct export market research. Methods of the activity began with coordination, mentoring, training, and evaluation for six months. Market research enabled two partners to identify three target countries for lurik fabric exports and three destination countries for virgin coconut oil. The first partner should choose Turkey's main export market of lurik fabrics, where there are 469 potential importers. The second partner should concentrate on exporting VCO to China, which has 13 importers. Both parties would face difficulties in selecting the appropriate importers to offer their export products of lurik fabric and virgin coconut oil at competitive prices. The next activity on the agenda is to assist partners in selecting potential importers and calculating the export price of competitive products.